2019
DOI: 10.5430/ijhe.v9n1p44
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes towards Sustainable Development among Malaysian Undergraduates

Abstract: This paper reports the findings of the perceptions and attitudes towards sustainable development among Malaysian undergraduates. The study was carried out involving 154 undergraduates from five universities in Malaysia. This research was conducted based on a survey whereby the respondents were given a questionnaire to gauge their perception and attitude towards sustainable development. The output of the analyses showed that the respondents have positive perceptions and attitudes towards all sustainability dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 21 publications
3
29
1
Order By: Relevance
“…Moreover, Saiz and Donald (2017) specified that the economic dimension of SD has not been given priority in ESD compared to the other dimensions of SD in most HEIs. Balakrishnan et al (2020) also found that Malaysian undergraduates from various disciplines lacked appropriate attitudes and perceptions toward economic sustainability issues.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, Saiz and Donald (2017) specified that the economic dimension of SD has not been given priority in ESD compared to the other dimensions of SD in most HEIs. Balakrishnan et al (2020) also found that Malaysian undergraduates from various disciplines lacked appropriate attitudes and perceptions toward economic sustainability issues.…”
Section: Resultsmentioning
confidence: 97%
“…The measurement model of geo-education among trainee teachers in Malaysia (Mat Rahimi Yusof) 717 the concept of sustainable education in the environment also causes this is not given good emphasis [33]. Table 3 showed the value of FL, CR, AVE and √ AVE for the primer constructs (FL=0.817-0.932, CR=0.941, AVE=0.761, SQRT AVE=0.872).…”
Section: Resultsmentioning
confidence: 99%
“…Sustainable development consists of three core dimensions related to quality of life: social, economic and environmental. A study reported on the current perception of environmental aspects and attitudes towards sustainable development among Malaysian undergraduates [5]. The questionnairebased study was conducted with 154 respondents from five universities in Malaysia and it examined their perception and attitude towards sustainable development.…”
Section: Ethical Commitmentmentioning
confidence: 99%